Analisis Fungsi Kalimat Imperatif dalam Kehidupan Sehari-Hari di Kampus Universitas Pgri Pontianak PBSI Kelas A Sore Semester 4 (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the function of imperative sentences in everyday life on the campus of Universitas PGRI Pontianak, specifically among students of PBSI Class A Afternoon Semester 4. This study uses a pragmatic approach to understand how imperative sentences are used in the context of campus communication. The results show that imperative sentences are used in various language functions, such as giving instructions, asking for help, and showing politeness. This study also finds that the use of imperative sentences can affect social relationships and communication between individuals on campus. The results of this study are expected to contribute to the understanding of the use of imperative sentences in the context of campus communication and can serve as a reference for further research on pragmatics and communication.